Vascular Access Tracking System: a Web-Based Clinical Tracking Tool for Identifying Catheter Related Blood Stream Infections in Interventional Radiology Placed Central Venous Catheters. - Morrison, James; Kaufman, John (Journal of Digital Imaging, 2016)
Vascular access is invaluable in the treatment of hospitalized patients. Central venous catheters provide a durable and long-term solution while saving patients from repeated needle sticks for peripheral IVs and blood draws. The initial catheter placement procedure and long-term catheter usage place patients at risk for infection. The goal of this project was to develop a system to track and evaluate central line-associated blood stream infections related to interventional radiology placement of central venous catheters. A customized web-based clinical database was developed via open-source tools to provide a dashboard for data mining and analysis of the catheter placement and infection information. Preliminary results were gathered over a 4-month period confirming the utility of the system. The tools and methodology employed to develop the vascular access tracking system could be easily tailored to other clinical scenarios to assist in quality control and improvement programs.